The Literal Translation of Sclerometer User Manual from Chinese to Indonesia - Stephanie Phanata; Juairiah Nastiti Sandyaningrum; Maela Vitalia (Mandarinable: Journal of Chinese Studies, 2022)
The linguistic style and the readers are two vital aspects to consider in applying the literal translation of the ‘Sclerometer User Manual’. These two aspects determine the word choices and their equivalents for the translation of the text to be well perceived by the readers. The descriptive qualitative method was employed for this study with two data sources, the primary data source which was the machine manuals in Chinese and the secondary data source from the documentation. In the process of language transfer, knowledge about Sclerometer, industrial and engineering vocabularies, and understanding of the text to be translated were highly required.